Analisa Kepuasan dan Kualitas Pelayanan Pelanggan Pada Pemesanan Makanan Menggunakan Metode Servqual - Ananti Putri Safira; Antonia Desya; Chelsy Zanedfi; Pebro Vaulina Rajagukguk; Malika Shakira; Izza Maulida; Eva Zuraidah (TIN: Terapan Informatika Nusantara, 2023)
So that in the future the decline in the number of customers can be minimized it is hoped that the number of customers will continue to increase to identify aspects of service quality that influence consumer perceptions of Nako coffee, as well as the extent of the gap between consumers' expectations and real experiences in consuming this coffee. .the aim of this research is to increase the coffee industry's understanding of marketing and product development while contributing to improving service quality in this specific coffee context. Servqual methodology is used as a research framework to measure dimensions of service quality, involving consumer surveys and statistical analysis to evaluate perceptions consumers are expected to provide in-depth insight into consumers' expectations and perceptions of Nako coffee, providing a basis for coffee industry stakeholders to improve marketing and service strategies. The influence of customer satisfaction when seen from the quality of service that has been met and must be maintained, but if seen from satisfaction There is a gap between customer expectations and the reality of the service received with a value of less than 1, so it can be said that customer satisfaction is still not optimal. There is a gap in reliability and assurance, the value of the gap is minus because expectations are greater than reality, while tangible, responsiveness, and empathy the reality assessment is greater than expectations, there are no negatives, then the quality of the product and service as assessed by customers is good.